Published research studies conducted amongst Indian medical undergraduate students: Bibliometric Analysis - Sachdeva, Sandeep; Sachdev, T R; Sachdeva, Ruchi; Dwivedi, Nidhi; Taneja, Neha (Indian Journal of Community Health, 2017)
Objective: Evaluation of published original research conducted amongst Indian medical undergraduate students. Methodology: A systematic review was undertaken using keywords “MBBS students” or “medical students” or “health students” or “university students” and “India” through search engines, PUBMED and Google scholar. Considering feasibility, time frame of published original research article was restricted to one-year only i.e. 2016. Research domain, research design, author and other bibliometric details of research manuscript were captured using check-list and analysis carried out using descriptive statistics. Results: A total of 99 suitable original research articles were identified under certain criteria and considered in present analysis. With regard to thematic research domain, highest, 29 (29.2%) articles were related to teaching and learning process followed by 13 (13.1%) to mental health (depression, anxiety, sleep, spirituality) of students; 07 (7.0%) were based on physical fitness/ exercise/yoga; and substance abuse (6.0%) amongst medical students etc. Nearly, 86 (86.8%) of articles were cross-sectional descriptive based studies while 13 (13.1%) had intervention based research design. A total of 34 (34.3%) research articles could be labeled as “KAP” (knowledge, attitude and practice) survey. Department wise detail of corresponding author was largely dominated by faculty from pre and para-clinical departments. Highest was community medicine in (35.3%) articles, pharmacology (23.2%), physiology (17.1%), microbiology (6.0%), and biochemistry (4.0%) etc. The studies covered an average sample size of 188.8 MBBS students (20-360, range); 57.5% of research article covered students from only one professional year. However, in 42 (42.4%) articles there was no further mention of gender based sample information. Out of all the references used in research articles, only 57.3% were of recent (2005-2015) origin while the rest were from older time-frame. Conclusion: A systematic evaluation of published original research articles conducted upon MBBS undergraduate students studying in Indian medical colleges was undertaken, probably first of its kind in India. In conclusion, diverse topics of research have been conducted by the teaching faculties and this study provides the over-view of the same